Nonwoven fabric and filter medium of air filter
Patent Information
- Application Number
- JP2023136991
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0010】 本発明によれば、高捕集効率と低圧力損失を兼ね備えた、エアフィルター濾材に好適な不織布を得ることができる。
Smart Images

Figure 2025031040000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonwoven fabric suitable for an air filter medium and to an air filter medium. [Background technology]
[0002] In recent years, there has been an increasing demand for cleaning spaces, and air filters that remove fine dust particles from the air are being used in a wide range of fields from living environments to industry, such as measures against health problems caused by dust particles with a particle size of 2.5 μm or less, and dust-free manufacturing of semiconductors and pharmaceuticals. In particular, in spaces that require extremely clean air, such as clean rooms and semiconductor manufacturing equipment, high-performance air filters such as HEPA filters (High Efficiency Particulate Air filters) and ULPA filters (Ultra Low Penetration Air filters) are used.
[0003] Conventionally, air filter media for HEPA filters and ULPA filters have been made of glass fiber nonwoven fabrics and PTFE (polytetrafluoroethylene) porous membranes. However, both air filter media made of glass fiber nonwoven fabrics and PTFE porous membranes are disposed of in landfills after use, which poses a large environmental burden.
[0004] In response to the recent increase in environmental awareness, various nonwoven fabrics have been proposed that are made of ultrafine polyester fibers and have excellent filtering properties, which have a smaller environmental impact.
[0005] For example, Patent Document 1 proposes an air filter medium using a nonwoven fabric containing three types of polyester fibers: nanofibers with a fiber diameter of 200 to 800 nm, fibers thicker than the nanofibers, and binder fibers. According to this proposal, it is possible to provide an air filter medium that has excellent pleatability and wind pressure deformation resistance, low pressure loss, and high collection performance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-140495 A Summary of the Invention [Problem to be solved by the invention]
[0007] The method described in Patent Document 1 can produce a nonwoven fabric that has excellent pleating properties and resistance to deformation due to wind pressure, but it does not achieve the collection efficiency required for HEPA filters or ULPA filters, and is also insufficient in terms of achieving both low pressure loss and high collection efficiency.
[0008] An object of the present invention is to solve the above-mentioned problems of the conventional technology and to provide a nonwoven fabric which combines high collection efficiency and low pressure loss and is suitable for use as an air filter medium, and an air filter medium using the same. [Means for solving the problem]
[0009] (1) A nonwoven fabric comprising organic fibers, characterized in that at least one type of organic fiber is a thick-thin fiber having alternating thick and thin portions and having 0.5 to 1,000 thick portions per mm. (2) The nonwoven fabric according to (1) above, characterized in that (fiber diameter of thick portion) / (fiber diameter of thin portion) is 1.1 to 10. (3) The nonwoven fabric according to (1) above, wherein the fiber diameter of the thin portions of the thick and thin fibers is 0.1 to 10 μm. (4) The nonwoven fabric according to (1) above, wherein the crystallinity of the thick portions of the thick and thin fibers is 20% or less. (5) The nonwoven fabric according to (1) above, wherein the nonwoven fabric is a wet-laid nonwoven fabric. (6) A laminated nonwoven fabric comprising the nonwoven fabric according to any one of (1) to (5) above and a breathable supporting material. (7) An air filter medium comprising the nonwoven fabric according to any one of (1) to (6). (8) An air filter using the air filter medium described in (7) above. (9) A fan filter unit equipped with the air filter described in (8) above. (10) A clean room or semiconductor manufacturing equipment equipped with the air filter described in (8) above. Effect of the Invention
[0010] According to the present invention, a nonwoven fabric that combines high collection efficiency and low pressure loss and is suitable for use as an air filter medium can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The nonwoven fabric of the present invention is a nonwoven fabric comprising organic fibers, characterized in that at least one type of organic fiber has thick parts and thin parts arranged alternately, and has 0.5 to 1,000 thick parts per mm.
[0012] The nonwoven fabric of the present invention will be described in detail below.
[0013] The thick and thin fibers used in the nonwoven fabric of the present invention have thick and thin fiber diameters arranged alternately. The thin parts of the thick and thin fibers of the present invention form a dense and three-dimensional structure, thereby exhibiting high collection performance. In addition, the thick parts of the thick and thin fibers of the present invention enter the dense and three-dimensional structure of the thin parts and become spacers to form voids in the nonwoven fabric, thereby reducing pressure loss when used as an air filter medium. The thick parts of the thick and thin fibers of the present invention can be formed by leaving unstretched parts locally when stretching organic fibers, or by mixing particles into the raw material in advance when spinning. That is, the thin parts of the thick and thin fibers of the present invention are the stretched parts of the fibers and the parts where particles are not included in the raw material.
[0014] The thick and thin fibers of the present invention are preferable because the more thick parts there are, the more voids there are, and the pressure loss can be reduced. However, if there are too many thick parts, the thin fibers cannot be arranged densely, and the collection performance decreases. Therefore, if the number of thick parts is 1000 or less per mm, high collection performance can be maintained in addition to low pressure loss. It is more preferable that the number of thick parts is 500 or less per mm. On the other hand, if there are few thick parts, the voids are reduced and the pressure loss increases. Therefore, if the number of thick parts is 0.5 or more per mm, voids can be secured and pressure loss can be reduced. It is more preferable that the number of thick parts is 2 or more per mm, and even more preferable that it is 5 or more per mm.
[0015] The thick-thin fiber of the present invention is preferably such that the ratio of the fiber diameter of the thick part to the thin part [(fiber diameter of the thick part) / (fiber diameter of the thin part)], i.e., the thick-thin ratio, is larger, because the larger the voids formed are and the smaller the pressure loss is. Therefore, if the thick-thin ratio is 1.1 or more, it is possible to provide sufficient voids. On the other hand, the smaller the thick-thin ratio is, the smaller the voids formed are and the larger the pressure loss is, but if the thick-thin ratio is 10 or less, it is possible to achieve both high collection efficiency due to the thin parts of the thick-thin fiber and suppression of pressure loss. The thick-thin ratio is more preferably 7 or less, and even more preferably 5 or less.
[0016] The thick and thin fibers of the present invention are preferable because the smaller the fiber diameter of the thin part, the higher the specific surface area becomes, and the higher the collection performance is exhibited when made into a nonwoven fabric. If the fiber diameter of the thin part is 10 μm or less, the effect of the high specific surface area due to the small fiber diameter will result in excellent collection performance when made into a nonwoven fabric. The fiber diameter of the thin part is more preferably 7 μm or less, and even more preferably 5 μm or less. On the other hand, if the fiber diameter of the thin part is 0.1 μm or more, in addition to high collection performance, the nonwoven fabric will have good handleability and moldability during processing, and it is possible to obtain a nonwoven fabric with excellent durability during use. The fiber diameter of the thin part is more preferably 0.15 μm or more.
[0017] The cross-sectional shape of the thick and thin fibers of the present invention is not particularly limited, and examples of such shapes include a perfect circular cross section, an ellipse, a polygon, a flattened shape, a cross shape, an X-shape, and a Y-shape, but is not limited to these.
[0018] The thick and thin fibers of the present invention can be used as a binder by making the crystallinity of the thick part of the fiber 20% or less as the undrawn part. Since it is the same polymer as the crystallized thin part, when the thick part is softened and fluidized by heat treatment, it is easy to blend due to the same composition, and it is possible to strongly and uniformly bond between the fibers.
[0019] The nonwoven fabric of the present invention may further contain aggregates (aggregate fibers) for reducing pressure loss and for maintaining the shape of the nonwoven fabric, and microfibers can be used as the aggregates. If the fiber diameter of the microfiber is 1 to 50 μm, it is preferable because it has high collection performance, as well as good handleability and moldability during nonwoven fabric processing.
[0020] In addition, the nonwoven fabric of the present invention can use various binders such as fibrous or adhesive binders to physically bond the fibers constituting the nonwoven fabric together by thermal adhesion. The binder in this case is not particularly limited, but for example, a core-sheath fiber in which a thermoplastic polymer having a melting point of 150°C or less is arranged in the sheath can be preferably used. When such a core-sheath fiber is used, after the nonwoven fabric is formed, the sheath component on the surface of the binder fiber is melted and bonded to other fibers constituting the nonwoven fabric by a drying process such as a Yankee dryer or an air-through dryer, or a heat treatment process such as a calendar, which is preferable because it can increase the rigidity of the nonwoven fabric. Furthermore, it is preferable because the core component of the binder fiber can contribute to ensuring the strength of the nonwoven fabric. Note that if the melting point of the core component of the binder fiber is higher than the melting point of the sheath component and the difference between the melting points is 20°C or more, the sheath component on the surface of the binder fiber is easily melted sufficiently, and the decrease in the orientation of the core component is suppressed, and sufficient thermal adhesion and high rigidity can be achieved at the same time, which is preferable.
[0021] All of the fibers used in the nonwoven fabric of the present invention are organic fibers. The organic fibers in the present invention are fibrous materials mainly composed of organic matter. Specific examples of organic fibers include, but are not limited to, cellulose produced from wood pulp, natural fibers such as cotton, hemp, wool, and silk, regenerated fibers such as rayon, semi-synthetic fibers such as acetate, and synthetic fibers such as polyester, nylon, and acrylic. Among them, synthetic fibers made of thermoplastic polymers are preferable from the viewpoint of mechanical properties and dimensional stability. Specific examples of thermoplastic polymers include polyesters such as polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polylactic acid, polyamides such as polyamide 6, polyamide 66, and polyamide 610, polyolefins such as polyethylene, polypropylene, and polymethylpentene, thermoplastic polymers such as polycarbonate, polyacrylate, polyphenylene sulfide, and thermoplastic polyurethane, and copolymers thereof. Among these, polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate, polyamides such as polyamide 6 and polyamide 66, and polyphenylene sulfide are preferred because they combine mechanical properties and heat resistance.
[0022] The organic fiber in the present invention may be modified in various ways by adding secondary additives, as long as the effect of the present invention is not impaired. Specific examples of secondary additives include, but are not limited to, compatibilizers, plasticizers, antioxidants, ultraviolet absorbers, infrared absorbers, fluorescent whitening agents, release agents, antibacterial agents, nucleating agents, heat stabilizers, flame retardants, antistatic agents, coloring inhibitors, regulators, matting agents, defoaming agents, preservatives, gelling agents, latexes, fillers, inks, colorants, dyes, pigments, and fragrances. These secondary additives may be used alone or in combination.
[0023] The weight of the nonwoven fabric of the present invention is 3 to 100 g / m 2 The basis weight of the nonwoven fabric in the present invention refers to a value measured by the method described in the Examples section.2 If the density is more than 5 g / m, a uniform nonwoven fabric with little density difference and excellent durability during use can be obtained, which is preferable. 2 More preferably, it is 7 g / m or more. 2 It is more preferable that the basis weight is 100 g / m or more. 2 If the weight is less than 80 g / m, the handling property and moldability during nonwoven fabric processing are good, which is preferable. 2 More preferably, it is 50 g / m or less. 2 It is even more preferable that:
[0024] The thickness of the nonwoven fabric of the present invention is preferably 0.01 to 1.0 mm. The thickness of the nonwoven fabric in the present invention refers to a value measured by the method described in the Examples section. If the thickness is 0.01 mm or more, the nonwoven fabric has good handleability and moldability during processing, and is therefore preferable because it is possible to obtain a nonwoven fabric with excellent durability during use. The thickness is more preferably 0.02 mm or more. On the other hand, if the thickness is 1.0 mm or less, it is preferable because it is possible to suppress high pressure loss due to densification of the nonwoven fabric. The thickness is more preferably 0.9 mm or less, and even more preferably 0.8 mm or less.
[0025] Next, an example of a method for producing the nonwoven fabric of the present invention will be described below.
[0026] When using fibers other than the thick and thin fibers of the present invention (microfibers, binder fibers, etc.), the fibers are put into an aqueous medium and stirred with a disintegrator to prepare a fiber dispersion that is uniformly dispersed. In this process, the dispersibility of the fibers can be adjusted by the amount of fiber charged, the amount of aqueous medium, stirring time, etc., and it is preferable that each short fiber is dispersed as uniformly as possible in the aqueous medium. A dispersant may be added to improve the dispersibility of the fibers in the aqueous medium, but it is preferable to keep the amount of dispersant added to a minimum necessary amount so as not to affect the processability when the nonwoven fabric is subjected to post-processing.
[0027] Next, a fiber dispersion in which the thick and thin fibers are uniformly dispersed in an aqueous medium is prepared according to the method described below. This fiber dispersion is mixed with a fiber dispersion of fibers other than the thick and thin fibers described above to obtain a papermaking stock solution, which is then wet-laid to obtain a nonwoven fabric in which the fibers constituting the nonwoven fabric are uniformly arranged.
[0028] The thick and thin fibers of the present invention can be produced by using a sea-island fiber made of two or more polymers with different dissolution rates in a solvent. The sea-island fiber of the present invention is a fiber having a structure in which island components made of a poorly soluble polymer are scattered in a sea component made of a readily soluble polymer. The thick and thin fibers are obtained by dissolving the sea component to leave only the island components.
[0029] The preferred method for spinning the sea-island composite fiber is melt spinning, which is highly productive and allows continuous production. Furthermore, a method using a sea-island composite spinneret is preferred, as it allows excellent control of the fiber diameter and cross-sectional shape of the island component fibers.
[0030] Specific examples of the poorly soluble polymer used for the island components in the present invention include, but are not limited to, polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polylactic acid; polyamides such as polyamide 6, polyamide 66, and polyamide 610; polyolefins such as polyethylene, polypropylene, and polymethylpentene; thermoplastic polymers such as polycarbonate, polyacrylate, polyphenylene sulfide, and thermoplastic polyurethane; and copolymers thereof.
[0031] From the viewpoint of simplifying the dissolution step of the sea component, the readily soluble polymer used in the present invention is preferably readily soluble in an aqueous solvent, hot water, etc. As the readily soluble polymer in the present invention, it is preferable to use a copolymerized polyester, polylactic acid, polyvinyl alcohol, etc., and in particular, it is preferable to use a polyester copolymerized with polyethylene glycol or sodium 5-sulfoisophthalate alone or in combination, or polylactic acid, from the viewpoints of ease of handling and easy dissolution in a low-concentration aqueous solvent.
[0032] In the present invention, "easily soluble" means that, when the poorly soluble polymer is used as a standard in the solvent used for the dissolution treatment, the dissolution rate ratio (easily soluble polymer / poorly soluble polymer) is 100 or more. In consideration of simplifying the dissolution treatment and shortening the time, this dissolution rate ratio is preferably large, and the dissolution rate ratio is more preferably 1000 or more, and even more preferably 10000 or more. If it is within this range, the dissolution treatment is completed in a short time, and thick and thin fibers suitable for the present invention can be obtained without unnecessarily deteriorating the poorly soluble polymer, which is preferable.
[0033] From the viewpoints of solubility in aqueous solvents and simplification of waste liquid treatment generated during dissolution, polyesters copolymerized with 3 to 20 mol % of polylactic acid, sodium 5-sulfoisophthalate, and polyesters copolymerized with 5 to 15 wt % of polyethylene glycol having a weight average molecular weight of 500 to 3,000 in addition to the aforementioned sodium 5-sulfoisophthalate are particularly preferred.
[0034] In view of the above, examples of suitable polymer combinations for the above-mentioned sea-island fiber include, but are not limited to, a sea part made of either a polyester copolymerized with 3-20 mol% sodium 5-sulfoisophthalate and 5-15 wt% polyethylene glycol having a weight average molecular weight of 500-3000, or polylactic acid, and an island part made of either polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, or copolymers thereof.
[0035] The spinning temperature of the sea-island composite fiber is preferably set to a temperature at which the poorly soluble polymer and the easily soluble polymer, mainly those with high melting points and high viscosity, show fluidity, as determined from the above-mentioned viewpoints. The temperature at which fluidity is shown varies depending on the properties and molecular weight of the polymer, but the melting point of the polymer is a guide, and the spinning temperature may be set to the melting point + 60°C or lower. This range is preferable because it prevents thermal decomposition of the polymer in the spinning head or spinning pack, prevents molecular weight reduction, and allows for good production of the sea-island composite fiber.
[0036] As described above, in order to dissolve and remove the sea part from the sea-island composite fiber to obtain ultrafine fibers, the sea-island composite spinneret exemplified in Japanese Patent No. 5740877 can be preferably used in the present invention, but is not limited thereto.
[0037] The melted yarn extruded from the sea-island composite spinneret is cooled and solidified, and converged by adding an oil, and taken up by rollers with a specified peripheral speed. The take-up speed can be determined based on the discharge rate and the target fiber diameter, and is preferably 100-7000 m / min from the viewpoint of stable production of the sea-island fiber. This undrawn sea-island fiber is a sea-island fiber in which thick parts and thin parts are arranged alternately. Specifically, the operating air pressure is 0.5-5 kg / cm between the first delivery roller and the second delivery roller via a feed roller. 2 Using the fluid swirl nozzle, the running yarn is drawn at a low draw ratio of 1.05 to 1.7 times while generating knotted balloons in the yarn, and then the yarn is heat set at 80 to 180°C by the second delivery roller, and then wound up into an islands-in-sea fiber with alternating thick and thin segments.
[0038] The sea-island composite fiber having the thick and thin portions alternately arranged is preferably cut into a tow of several tens to several millions of fibers using a cutting machine such as a guillotine cutter, a slicer, or a cryostat to a desired fiber length. The fiber length after cutting is preferably cut so that the ratio (fiber length / fiber diameter) of the diameter of the island component of the sea-island composite fiber (corresponding to the fiber diameter of the ultrafine fiber) is 1000 to 6000. This range is preferable because the number of contact points between the fibers increases when the fiber is made into a nonwoven fabric, which promotes the formation of a bridge structure between the fibers and enhances the reinforcing effect of the nonwoven fabric. A fiber length / fiber diameter of 1000 or more is preferable because the ultrafine fibers are prevented from falling off from the nonwoven fabric during the nonwoven fabric processing by wet papermaking. The fiber length / fiber diameter is more preferably 1500 or more, and even more preferably 2000 or more. On the other hand, if the fiber length / fiber diameter is 6000 or less, aggregation of the ultrafine fibers in an aqueous medium is suppressed, and a nonwoven fabric with high uniformity can be obtained, which is preferable. The fiber length / fiber diameter is more preferably 5500 or less, and even more preferably 5000 or less.
[0039] By dissolving and removing the sea part from the above-mentioned sea-island fiber, ultrafine fibers with thick and thin parts arranged alternately can be produced. That is, the above-mentioned cut sea-island fiber is immersed in a solvent capable of dissolving the soluble polymer of the sea part to remove the soluble polymer. When the soluble polymer is copolymerized polyethylene terephthalate or polylactic acid in which sodium 5-sulfoisophthalate or polyethylene glycol is copolymerized, an alkaline aqueous solution such as an aqueous sodium hydroxide solution can be used. When using an alkaline aqueous solution, the bath ratio of the sea-island fiber to the alkaline aqueous solution (weight (g) of the sea-island fiber:weight (g) of the alkaline aqueous solution) is preferably 1:5 to 1:10000, more preferably 1:10 to 1:5000. This range is preferable because it prevents the ultrafine fibers from being unnecessarily entangled when the soluble polymer of the sea part is dissolved.
[0040] The alkali concentration of the alkaline aqueous solution is preferably 0.1 to 5 wt%, more preferably 0.5 to 3 wt%. This range is preferable because dissolution of the easily soluble polymer of the sea component is completed in a short time, and a fiber dispersion in which ultrafine fibers are uniformly dispersed can be obtained without unnecessarily deteriorating the poorly soluble polymer of the island component. The temperature of the alkaline aqueous solution is not particularly limited, but is preferably 50°C or higher, because the dissolution of the easily soluble polymer of the sea component can be accelerated.
[0041] In the present invention, the aqueous solution of the easily soluble polymer of the sea part from the sea-island fiber may be used as it is as a fiber dispersion of ultrafine fibers, or may be used after adjusting the pH by adding an acid or an alkali, or after diluting with water. A dispersant may be added to the fiber dispersion to suppress aggregation of the ultrafine fibers over time. The dispersant may be a cationic compound, a nonionic compound, an anionic compound, or the like. Among them, an anionic compound is preferred from the viewpoint of improving dispersibility due to electrical repulsion in an aqueous medium. The amount of the dispersant added is preferably 0.001 to 10 times the weight of the fibers, and within this range, the dispersibility of the fibers is ensured without impairing the processability during nonwoven fabric processing by wet papermaking, which is preferable.
[0042] In the present invention, the fibers other than the thick and thin fibers (microfibers, binder fibers, etc.) can be produced by melt spinning using a known method, stretching as necessary, and then cutting to a desired fiber length as described above. Here, the fiber length of the fibers other than the thick and thin fibers is preferably 30 mm or less. If the fiber length is 30 mm or less, the formation of fiber agglomerates caused by the fibers being strongly entangled with each other during dispersion in an aqueous medium is suppressed, a homogeneous nonwoven fabric can be obtained, and the nonwoven fabric can be suitably used as an air filter medium, which is preferable.
[0043] The fiber dispersion of ultrafine fibers thus prepared is mixed with the fiber dispersion of fibers other than ultrafine fibers, and diluted to a certain concentration to prepare a papermaking stock solution, which is then dehydrated on an inclined wire or cylinder to form a nonwoven fabric by wet papermaking. Apparatuses used for wet papermaking include, but are not limited to, cylinder papermaking machines, fourdrinier papermaking machines, inclined short wire papermaking machines, or combinations of these. In the papermaking process, a three-dimensionally homogenous nonwoven fabric can be produced by controlling the accumulation of fibers during drainage by adjusting the papermaking speed and the amount of fibers and aqueous medium in addition to the dispersibility of fibers in the papermaking stock solution.
[0044] The nonwoven fabric formed by wet papermaking is subjected to a drying process to remove moisture. As a drying method, a method using hot air ventilation (air through) or a method of contacting with a heated rotating roll (heated calendar roll, etc.) can be suitably adopted from the viewpoint of simultaneously drying the nonwoven fabric and thermally bonding the thermally adhesive fibers.
[0045] The nonwoven fabric of the present invention can be a laminated nonwoven fabric having a breathable support material laminated on both sides. The material and structure of the breathable support material are not particularly limited, but for example, a nonwoven fabric, a woven fabric, a metal mesh, a resin net, etc. are used. Among them, a dry nonwoven fabric having heat fusion properties is preferable in terms of strength, collection ability, flexibility, and workability. Furthermore, the dry nonwoven fabric may be a nonwoven fabric in which some or all of the fibers constituting it have a core / sheath structure, or a two-layer nonwoven fabric consisting of two layers of a low melting point material and a high melting point material. The material of the dry nonwoven fabric is not particularly limited, and polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polylactic acid, polyamides such as polyamide 6, polyamide 66, and polyamide 610, polyolefins such as polyethylene, polypropylene, and polymethylpentene, thermoplastic polymers such as polycarbonate, polyacrylate, polyphenylene sulfide, and thermoplastic polyurethane, and copolymers or composites thereof can be used. In the dry nonwoven fabric having a core / sheath structure, the core component preferably has a higher melting point than the sheath component. For example, the combination of the core / sheath materials may be, for example, polyethylene terephthalate / polyethylene, or high melting point polyethylene terephthalate / low melting point polyethylene terephthalate. The breathable support material can be bonded to the nonwoven fabric of the present invention by partially melting the breathable support material by heating, or by melting a hot melt resin, by utilizing the anchor effect, or by utilizing adhesion such as a reactive adhesive.
[0046] The basis weight and thickness of the breathable support material are not particularly limited and may be the same or different on both sides of the nonwoven fabric of the present invention. The nonwoven fabric of the present invention may be a single layer or a multi-layer in which multiple sheets are stacked. In this case, the multiple sheets of the nonwoven fabric of the present invention may be of the same type, and a breathable support material may be sandwiched between them. In another embodiment, the breathable support material may be laminated only on one side of the nonwoven fabric of the present invention.
[0047] In order to extend the life of the laminated nonwoven fabric, a pre-collection layer may be further laminated on the breathable support material on one side (usually the upstream side of the airflow passing through the filter medium). As the pre-collection layer, for example, one obtained by the melt blowing method is used. Examples of the material of the pre-collection layer include polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polylactic acid, polyamides such as polyamide 6, polyamide 66, and polyamide 610, polyolefins such as polyethylene, polypropylene, and polymethylpentene, thermoplastic polymers such as polycarbonate, polyacrylate, polyphenylene sulfide, and thermoplastic polyurethane, and copolymers thereof. The pre-collection layer can be bonded to the laminated nonwoven fabric by thermal lamination using, for example, a hot melt resin.
[0048] The nonwoven fabric of the present invention has both high collection efficiency and low pressure loss, so the air filter material using the nonwoven fabric of the present invention can be suitably used as an air filter material for air purifiers, air conditioners, building air conditioners, industrial clean rooms, and car compartments of automobiles, trains, etc. In addition, in spaces that require extremely clean air, such as clean rooms and semiconductor manufacturing equipment, the air filter material can be suitably used as an air filter material for air conditioners that take in outside air into clean rooms, air conditioners that circulate air in clean rooms, and air filters for fan filter units installed on the ceilings of clean rooms and semiconductor manufacturing equipment. Clean rooms and semiconductor manufacturing equipment equipped with air filters using these air filter materials of the present invention are useful in various industries. EXAMPLES
[0049] The present invention will now be described in detail with reference to examples. However, the present invention is not limited to these examples. The respective property values in the examples were determined by the following methods.
[0050] A. Fiber diameter of thick and thin parts The nonwoven fabric obtained in the examples and comparative examples was used as a sample, and images of the surface of the nonwoven fabric were taken with a scanning electron microscope (SU-1510 manufactured by Hitachi High-Technologies Corporation) at a magnification that allowed observation of 300 to 3000 fibers, and the fiber diameters of the thick and thin parts of 100 thick and thin fibers randomly extracted from the taken images were measured. Regarding the fiber diameter, the fiber width in the direction perpendicular to the fiber axis was taken from the two-dimensionally taken image, and the thick and thin parts were measured in μm units to three decimal places. The above operation was performed on 10 images taken in the same manner, and the fiber diameters of the thick and thin parts of the thick and thin fibers were determined from a total of 1000 fibers measured from the 10 images.
[0051] B. Number of thick parts per mm The nonwoven fabric used in the measurement of item A above was used as a sample, and an image of the surface of the nonwoven fabric was taken with a scanning electron microscope (SU-1510 manufactured by Hitachi High-Technologies Corporation) at a magnification that allowed observation of 300 to 3000 fibers. For 100 fibers randomly extracted from the image, the distance between two thick parts of each thick and thin fiber was measured. The distance was measured from the center of the first thick part to the center of the second thick part in the same axial direction to the fiber axis in the two-dimensionally taken image in μm units to the first decimal place. 1000 μm (= 1 mm) was divided by the above distance and measured. Number of thick parts per mm (pieces) = 1000 (μm) / distance between two thick parts (μm) The above procedure was carried out for 10 images taken in the same manner, and the number of thick parts per mm was calculated from a total of 1,000 fibers measured from the 10 images.
[0052] C. (Fiber diameter of thick part) / (Fiber diameter of thin part) Using the fiber diameters of the thick and thin parts calculated in A above, calculate the following formula: [(Fiber diameter of thick part) / (Fiber diameter of thin part)]=[Fiber diameter of thick part (μm)] / [Fiber diameter of thin part (μm)] It was calculated by:
[0053] D. Crystallinity The nonwoven fabrics obtained in the examples and comparative examples were used as samples, and the 1730 cm peak attributable to the C=O stretching vibration of polyester was measured for the thick parts of the thick and thin fibers using a microscopic laser Raman spectrometer (Tokyo Instruments Nanofinder 30). -1 The full width at half maximum of the Raman band near 1730 The reduced density ρ in the formula below was empirically derived from the half-width of various PET samples. Converted density ρ(g / cm 3 )=(305-Δν 1730 ) / 209 Crystallinity (%)=100×(ρ-1.335) / (1.455-1.335) The measurement was carried out five times for each sample, and the average value was regarded as the degree of crystallinity.
[0054] E. Metsuke The nonwoven fabrics obtained in the Examples and Comparative Examples were used as samples. The nonwoven fabrics were cut into 250 mm × 250 mm squares, and the weights of the pieces were measured to determine the unit area (1 m 2 The weight per unit area of the nonwoven fabric (g / m2) is calculated by rounding off the value to the nearest tenth. 2 The measurements were carried out on three randomly selected points per sample, and the average value was rounded off to one decimal place to obtain the basis weight.
[0055] F. Thickness The nonwoven fabric used in the measurement of item E above was used as a sample, and the thickness of the nonwoven fabric was measured using a dial thickness gauge (TECLOCK Corp. SM-114, probe shape 10 mmφ, graduation 0.01 mm, measuring force 2.5 N or less). Measurements were taken at five random locations per sample, and the average value was rounded off to the fourth decimal place to calculate the thickness (mm) of the nonwoven fabric.
[0056] G. Porosity Using the basis weight and thickness of the nonwoven fabric calculated in items E and F above, the value calculated by the following formula was rounded off to one decimal place to determine the porosity (%) of the nonwoven fabric. Porosity (%) = 100 - [Weight (g / m 2) / {Thickness (mm) × Fiber density (g / cm 3 )}]×0.1 The fiber density should be the density of the fibers that make up the nonwoven fabric, and in the case of PET, it is 1.38 g / cm 3 It was calculated as:
[0057] H. Collection efficiency The nonwoven fabrics obtained in the examples and comparative examples were used as samples, with an effective opening area of 0.01 m 2 The nonwoven fabric was set in the holder, and polystyrene latex particles with an average particle size of 0.15 to 0.16 μm were blown in the vertical direction at a surface air velocity of 3.3 m / min at a rate of 10,000 to 25,000 particles / m 3 The number of atmospheric dust particles with a particle size of 0.15 μm upstream and downstream of the filter was measured using a particle counter (KC-22A, manufactured by RION Corporation), and the collection efficiency was calculated using the following formula. Collection efficiency (%) = 1-(number of downstream particles / number of upstream particles) x 100 The measurements were carried out using three samples, with one sample taken from one random location, and the average value was rounded off to two decimal places to obtain the collection efficiency (%).
[0058] I. Pressure loss The nonwoven fabrics obtained in the Examples and Comparative Examples were used as samples. The nonwoven fabrics were cut into circles with a diameter of 200 mm and an effective opening area of 0.1 m. 2 The filter was set in a holder, and air was passed vertically at a surface velocity of 3.3 m / min, and the pressure difference between the upstream and downstream of the filter was measured with a differential pressure gauge. Measurements were taken at three randomly selected points for each sample, and the average value was rounded off to the nearest tenth to obtain the pressure loss (Pa).
[0059] J. Performance indicators Using the collection efficiency and pressure loss of the nonwoven fabric calculated in items H and I above, the following formula is calculated: Performance index (1 / Pa) = -ln[{1-collection efficiency (%) / 100)} / pressure loss (Pa)] The value calculated by the above was rounded off to three decimal places to obtain the performance index of the nonwoven fabric (1 / Pa).
[0060] Example 1 Polyethylene terephthalate (PET) was used as island components, and copolymerized PET, which was copolymerized with 8.0 mol% sodium 5-sulfoisophthalate and 10 wt% polyethylene glycol with a molecular weight of 1000, was used as a sea component, and each was vacuum dried for 12 hours at 150° C. Then, the island components and sea components were fed to an extruder-type composite spinning machine in a blending ratio of 50 wt % and 50 wt % to be melted separately, and the resulting mixture was fed into a spinning pack incorporating a sea-island composite spinneret (number of island components: 2000, cross-sectional shape of island components: circular) at a spinning temperature of 285° C., and the composite polymer flow was discharged from the discharge hole at a discharge rate of 3 g / min to obtain a spun yarn. The spun yarn was cooled with cooling air at a temperature of 20°C and a speed of 20 m / min, oiled with an oiling device to make it converge, taken up by a first godet roller rotating at 1000 m / min, passed through a second godet roller rotating at the same speed as the first godet roller, and wound up by a winder to obtain an undrawn yarn. Thereafter, the undrawn yarn obtained was passed through a drawing machine between a first delivery roller at 85°C and a second delivery roller at 130°C, with an operating air pressure of 2 kg / cm. 2 The fiber was stretched 1.5 times using a fluid swirl nozzle to obtain an islands-in-the-sea fiber with alternating thick and thin segments.
[0061] The resulting sea-island fiber was cut to a fiber length of 0.6 mm, and then treated in a 1% by weight aqueous sodium hydroxide solution at a bath ratio of 1:100 at 90°C for 30 minutes, and neutralized to pH=7 with acetic acid to obtain a fiber dispersion.
[0062] The fiber dispersion was mixed homogeneously so that the fiber weight was 0.625 g to prepare a papermaking stock solution. The papermaking stock solution was wet-formed using a square sheet machine (250 mm square) manufactured by Kumagai Riki Kogyo Co., Ltd., and then heat-pressed at a pressure of 1.5 MPa for 3 minutes using a flat plate heating press at 80°C to obtain a nonwoven fabric.
[0063] The evaluation results of the obtained nonwoven fabric are shown in Table 1. The obtained nonwoven fabric had a basis weight of 9.9 g / m 2 and had a thickness of 0.048 mm.
[0064] Comparative Example 1 Except for removing the fluid rotating nozzles from the first delivery roller and the second delivery roller and changing the stretch ratio to 3.4 times, a nonwoven fabric was produced in the same manner as in Example 1. The evaluation results of the obtained nonwoven fabric are shown in Table 1.
[0065] In Comparative Example 1, since the fibers did not have thick and thin parts, the thickness was thinner and the porosity was lower than in Example 1. As a result, the pressure loss increased significantly. In addition, since the material that functions as a binder was not included, the nonwoven fabric could not be bonded by hot pressing, resulting in a weak nonwoven fabric.
[0066] [Table 1]
Claims
1. The nonwoven fabric is composed of organic fibers, and is characterized in that at least one type of fiber of the organic fibers is a thick-thin fiber having thick parts and thin parts arranged alternately and having 0.5 to 1,000 thick parts per mm.
2. 2. The nonwoven fabric according to claim 1, wherein the ratio of (fiber diameter of thick portion) / (fiber diameter of thin portion) of the thick and thin fibers is 1.1 to 10.
3. 2. The nonwoven fabric according to claim 1, wherein the fiber diameter of the thin portion of the thick and thin fibers is 0.1 to 10 μm.
4. 2. The nonwoven fabric according to claim 1, wherein the degree of crystallinity of the thick portions of the thick and thin fibers is 20% or less.
5. 2. The nonwoven fabric according to claim 1, which is a wet-laid nonwoven fabric.
6. A laminated nonwoven fabric comprising the nonwoven fabric according to any one of claims 1 to 5 and a breathable support material.
7. An air filter medium comprising the nonwoven fabric according to any one of claims 1 to 6.
8. An air filter comprising the air filter medium according to claim 7.
9. A fan filter unit comprising the air filter according to claim 8.
10. A clean room or semiconductor manufacturing equipment comprising the air filter according to claim 8.
Citation Information
Patent Citations
Wet nonwoven fabric and filter medium for air filter
JP2015140495A